The Relationship between Stress Level and Emotional Eating Behavior and Adolescent Nutritional Status at SMA Negeri 7 Gorontalo City - Tasmi S. Djafar; Vivien Novarina A. Kasim; Siti Hajar Salawali (Universitas Muhammadiyah Palu, 2026)
Adolescent nutritional status is an important indicator of health influenced by physical and psychosocial factors. In adolescence, academic stress and changes in eating behavior often contribute to the emergence of nutritional problems, both undernutrition and overnutrition. This condition is suspected to be related to stress levels and emotional eating behavior tendencies. This study aims to determine the relationship between stress levels and emotional eating behaviors with adolescent nutritional status at SMA Negeri 7 Gorontalo City. This study used a quantitative design with a cross sectional approach. The research sample amounted to 163 adolescents who were selected based on criteria, namely adolescents with a minimum level of stress in the mild category, not undergoing a diet program, and not having chronic diseases. Sample selection was taken using the Proportionate Stratified Random Sampling technique. This research instrument uses the Perceived Stress Scale (PSS-10) questionnaire and the Dutch Eating Behavior Questionnaire (DEBQ). Bivariate analysis using the Chi-Square test. The results showed a significant relationship between stress levels and nutritional status of adolescents (p-Value = 0.000). Meanwhile, there was a significant relationship between emotional eating behavior and adolescent nutritional status (p-Value = 0.000). It is hoped that it can be an information and evaluation material for adolescents, schools, and related parties in understanding the relationship between stress levels, emotional eating behaviors, and adolescent nutritional status. These findings can also serve as a basis for consideration in promotive and preventive efforts that focus on adolescent mental health and eating behavior in the school environment.